1979
DOI: 10.1128/aac.16.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and suppression of lymphocyte function in vitro

Abstract: The effects on the mitogenic response of human T lymphocytes were studied for 20 different antibiotics. No apparent inhibitory effect could be detected for penicillins, cephalosporins, aminoglycosides, chloramphenicol, sulfamethoxazole, trimethoprim, nalidixic acid, and 5-fluorocytosine. There were effects at high concentrations with erythromycin, clindamycin, and rifampin, and these antibiotics could also be shown to depress the mitogenic response of B lymphocytes. With fusidic acid, nitrofurantoin, and doxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Moreover, lipid-soluble tetracyclines have been reported to accumulate in leucocytes [9,41,42]. In agreement with the latter are the in vitro sludies that demonstrated that lipidsoluble tetracyclines are more potent inhibitors of mitogenindueed prohferation than non-lipid-soluble ones [13][14][15][16].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, lipid-soluble tetracyclines have been reported to accumulate in leucocytes [9,41,42]. In agreement with the latter are the in vitro sludies that demonstrated that lipidsoluble tetracyclines are more potent inhibitors of mitogenindueed prohferation than non-lipid-soluble ones [13][14][15][16].…”
Section: Discussionsupporting
confidence: 69%
“…the rejection of transplants [8][9][10][11] and levels of serum immunoglobulin [9,12]. Furthermore, in vitro tetracyclines inhibited the proliferative response of human peripheral blood mononuclear cells (PBMC) to mitogens [13][14][15][16].…”
Section: Introdljctionmentioning
confidence: 99%
“…In previous studies from our laboratory, we reported the inhibitory effects of various antibiotics on the mitogenic response of human lymphocytes (3,7,9). Some of these antibiotics (e.g., tetracyclines, rifampin, and fusidic acid) have also been shown to impair the immune response in vivo (4-6, 10, 12-14).…”
mentioning
confidence: 99%
“…It is possible that in certain tissues (such as liver) this effect is limited by failure of the drug to penetrate cells (Franklin, 1963), but this is unlikely to be important with human leucocytes since Brown & Percival (1978) have shown that their cell membranes are fairly permeable to these drugs. Banck & Forsgren (1979) have argued that tetracyclines act on mammalian cells by interference with protein synthesis. Potts et al (1983) have recently shown that doxycycine causes an almost insignificant reduction in early RNA synthesis, without interference with volume growth: the rate of recruitment of cells into the first S-phase is reduced and the cells increase in number at a slower rate than normal.…”
Section: Resultsmentioning
confidence: 99%
“…Certain tetracycline drugs (such as doxycycine and minocycine), but not others (such as tetracycline and oxytetracycline), suppress the growth of mitogenstimulated human lymphocytes when present in the culture fluid at concentrations comparable to peak blood levels sometimes achieved during treatment of infections (Banck & Forsgren, 1979;Thong & Ferranti, 1979). Finch (1980) has argued that it is unlikely that any of the tetracycline drugs will have an appreciable adverse effect on the immune response during the treatment of an acute infection in a previously healthy person since the duration of treatment with the antibiotic is short relative to the timecourse of the immunological reaction, but he has emphasized that the immunosuppressive effects of antimicrobial agents may be clinically relevant in long-term chemotherapy for chronic infections.…”
Section: Methodsmentioning
confidence: 99%